Electrostrictive Mechanism of Radiation Self-Action in Nanofluids - Albert Livashvili; Victor Krishtop; Margarita Yakunina (Advances in Condensed Matter Physics)
The electrostriction mechanism of beam self-focusing in nanofluids is theoretically investigated. An analytical solution of the diffusion equation, which describes the dynamics of particles in nanofluids, was obtained and studied. Explicit expressions for the nonlinear part of the refractive index and concentration lens focal length are presented. It is shown that there is a limit on the radiation intensity associated with the physical and hydrodynamic characteristics of the phenomena in these processes.